Tinjauan Pengawasan Terhadap Kinerja Karyawan dalam Konteks Ekonomi Islam: Studi Kasus pada Café Corner Bengkulu - Febi Vernanda; Romi Adetio Setiawan (Sekolah Tinggi Agama Islam Taruna Surabaya, 2023)
This research was undertaken with the objective of comprehending the efficacy of the supervision system at Cafe Corner Bengkulu in light of Islamic perspectives derived from the Al-Qur'an and Hadith. The research methodology employed in this investigation was a qualitative descriptive approach, specifically utilizing field research. The findings of this study indicate that the supervision system implemented by the leaders at this Café aligns with Islamic principles of supervision. This is evident through the application of several indicators of Islamic supervision, such as the consistent provision of bonuses to employees exhibiting high performance, thereby motivating other employees to maintain exemplary standards of work performance. Additionally, the supervision process involves various methods, including the use of CCTV cameras, telephonic communication, and regular evaluation meetings. In conclusion, it can be inferred that Café Corner Bengkulu has implemented an Islamic-based supervision system, with its leaders exemplifying Islamic principles of supervision. The findings of this research contribute to the development of insights into supervisory practices that could potentially be applicable in other contexts. Penelitian ini bertujuan untuk memahami efektifitas sistem pengawasan di Café Corner Bengkulu dalam perspektif Islam yang bersumber dari Al-Qur’an dan Hadis. Metode Penelitian yang digunakan adalah pendekatan deskriptif kualitatif dengan menggunakan penelitian lapangan. Hasil penelitian ini menunjukkan bahwa sistem pengawasan oleh pimpinan di Cafe ini telah sesuai dengan prinsip-prinsip pengawasan Islam. Hal ini dapat dilihat dari beberapa indikator pengawasan Islami yang telah diterapkan, yaitu pemilik usaha secara konsisten memberikan bonus kepada karyawan yang menunjukkan kinerja tinggi, sehingga memotivasi karyawan lainnya untuk menjaga standar kinerja yang baik. Selain itu, proses pengawan juga melibatkan beragam metode, termasuk penggunaan kamera CCTV, komunikasi via telpon, dan pertemuan evaluasi secara rutin. Dapat disimpulkan bahwa, Cafe Corner Bengkulu telah menerapkan sistem pengawasan berbasis Islam, dimana pemimpinnya mencontohkan prinsip-prinsip pengawasan Islam. Temuan pada penilitian ini memberikan kontribusi pada pengembangan wawasan mengenai praktik pengawasan yang juga mungkin bisa diterapkan pada konteks lainnya.